Seasonal variation in children with developmental dysplasia of the hip. (February 2014) - Loder, Randall T.; Shafer, Cody
Background: It has been postulated that developmental dysplasia of the hip (DDH) is more frequent in infants born in the winter months. It was the purpose of this study to ascertain if there was any seasonal variation in DDH at the author's institution and compare/contrast our results with those in the literature using rigorous mathematical fitting. Methods: All children with DDH treated at the author's institution from 1993 to 2012 were identified. The month of birth was recorded and temporal variation was analyzed using cosinor analysis. Similar data from the literature was analyzed. Results: There were 424 children (363 girls, 61 boys). An additional 22, 936 children were added from the literature for a total of 23, 360. Pearson's Chi-square test demonstrated a non-uniform distribution in the month of birth for both our 424 children as well as the combined literature series in both the Northern and Southern hemispheres. Cosinor analysis of the 424 children demonstrated double peaks in mid-March and mid-October. For the entire 23, 360 children, no seasonal variation was observed in 2, 205 (9.4 %), a single winter peak in 16, 425 (70.3 %), a single summer peak in 1, 280 (5.5 %), and double peaks in the spring and autumn in 3, 450 (14.8 %). Conclusions: This study partly supports the hypothesis of tight clothing/cold temperature as one factor in the etiology of DDH with the tighter clothing/swaddling increasing the risk of DDH. However ∼20 % of the DDH births demonstrated a non-winter peak. The single summer and double spring/autumn peaks, as well as in those series where no seasonal variation was noted, refutes the cold winter clothing hypothesis. Perhaps these different patterns in seasonal variation represent the heterogeneity of the genetic factors in DDH interacting with external factors (temperature and clothing) and internal factors (metabolic). Further study will be required to understand these different patterns in DDH seasonal variation. Level of evidence: IV—case series.